2012
DOI: 10.1002/j.1532-2149.2012.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain tolerance in children and adolescents: Sex differences and psychosocial influences on pain threshold and endurance

Abstract: Our results support the assumption that female and male adolescents develop in different directions regarding their pain tolerance when reaching puberty. This seems mainly attributable to a decrease of pain threshold in girls. In contrast, boys and girls are able to endure pain to an equal extent influenced, however, by self-efficacy and coping variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 18 publications
7
51
0
3
Order By: Relevance
“…As such, the presence of potential sex differences in those children who had undergone puberty may have been washed out because they were being considered along with pre-pubertal children. Previous research has had conflicting conclusions whether pubertal status or age is more important for understanding the development of sex differences in children's pain [62,90]. As pubertal status was only measured in two studies in the present review [3,64], age was used as a proxy, however, this was not ideal and future research is need to replicate our age-related findings.…”
Section: Sex Differences In Experimental Pain In Children 20mentioning
confidence: 86%
See 1 more Smart Citation
“…As such, the presence of potential sex differences in those children who had undergone puberty may have been washed out because they were being considered along with pre-pubertal children. Previous research has had conflicting conclusions whether pubertal status or age is more important for understanding the development of sex differences in children's pain [62,90]. As pubertal status was only measured in two studies in the present review [3,64], age was used as a proxy, however, this was not ideal and future research is need to replicate our age-related findings.…”
Section: Sex Differences In Experimental Pain In Children 20mentioning
confidence: 86%
“…Heat pain tasks showed more variability in effect sizes, from small for pain intensity and threshold (SMD = 0.07 and -0.31, respectively), to quite large for pain tolerance (SMD = -1.26).Pressure pain tasks demonstrated small effect sizes for pain intensity and threshold (SMD = 0.17 and -.035, respectively). Researchers may consider using the effect sizes from the present study in calculating sample sizes, should they wish to examine sex [90] recently demonstrated important future directions for the field through the inclusion of large sample sizes and methodology designed explicitly to examine sex differences across pubertal development. Researchers should consider conducting similar studies looking at additional pain outcomes (e.g., pain intensity) and using different experimental pain paradigms.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…Previous studies have shown that a child' s age, sex, and ethnicity are related to the child' s ability to describe pain, as well as the child' s perception and sensitivity to pain. [13][14][15][16][17][18][19] It is important, therefore, to determine whether the validity of the FPS-R and CAS varies in children based on their characteristics, and how suitable these scales are in different demographics.…”
mentioning
confidence: 99%
“…Lower pain threshold among women compared with men may explain part of the gender difference observed in the current study [34]. The lack of a significant association among healthy weight individuals also indicates that non-somatic symptoms, such weight-related anxiety, may potentially mediate the strong relationship between arthritis and depression among overweight adults.…”
Section: Discussionmentioning
confidence: 73%